Perbandingan Hukum Humaniter Internasional dan Hukum Humaniter Islam Terhadap Tawanan Perang - Rama Hadi Priyono; Rina Shahriyani Shahrullah (Fakultas Hukum, Universitas Internasional Batam, 2016)
Writing and this study to study and said problems on regulation of and comparison treatment a prisoner at law humaniter international and islamic law humaniter to treatment prisoner group Abu Sayyaf in South Philippines . This research including the kind of research normative law.The kind of data that used is taken from secondary data.Technique data collection be used for example through study literature. This research referring to the hague convention 1907 and the geneva convention 1949 where both this convention set about the war and more specifically about a prisoner of war .Then , superimposed on the source of islamic law is Al-qur’an and hadist against islamic views on war and there treatment in captivity .On the source is found the equation similarities and differences about the war and treatment hostages